THE IMPACT OF INFORMATION TECHNOLOGIES ON THE THINKING OF THE YOUNGER GENERATION - Abdusamadova Maftunaxon Abdusalomxuja qizi; Fakhriddin Urinboevich Toshboltaev (Ustozlar uchun, 2025)
This article provides a comprehensive analysis of the impact of information technologies on the thinking patterns of the younger generation. It explores how digital technologies, the internet, mobile devices, and social media influence the cognitive development of children and adolescents, highlighting both positive and negative aspects. On one hand, quick access to information, the enhancement of creative thinking, and the development of critical reasoning are emphasized as beneficial effects. On the other hand, the article also addresses potential drawbacks such as attention disorders, addiction to virtual environments, and social isolation. The article highlights both the positive and negative aspects of information technologies and outlines effective ways to utilize them in the educational process. The research findings indicate that the role of technology in shaping the thinking and cognitive development of young people is steadily increasing.